東南極、セール・ロンダーネ山地のベンゲン花崗岩とビキングヘグダ花崗岩のSr・Nd同位体組成 - 柚原, 雅樹; 亀井, 淳志; 川野, 良信; 大和田, 正明; 志村, 俊昭; 束田, 和弘; Yuhara, Masaki; Kamei, Atsushi; Kawano, Yoshinobu; Owada, Masaaki; SHIMURA, Toshiaki; Tsukada, Kazuhiro (2014)
conference object